2023
DOI: 10.3389/fimmu.2022.1108071
|View full text |Cite
|
Sign up to set email alerts
|

MAITabolism2 – the emerging understanding of MAIT cell metabolism and their role in metabolic disease

Abstract: Mucosal associated invariant T (MAIT) cells are a population of unconventional innate T cells due to their non-MHC restriction and rapid effector responses. MAIT cells can recognise bacterial derived antigens presented on the MHC-like protein via their semi-restricted T cell receptor (TCR). Upon TCR triggering MAIT cells rapidly produce a range of effector molecules including cytokines, lytic granules and chemokines. This rapid and robust effector response makes MAIT cells critical in host responses against ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 80 publications
0
1
0
Order By: Relevance
“…In contrast, they can also be activated in a TCR-independent manner, via stimulation with cytokines such as IL-18 7,8 . Recently, several studies have highlighted the importance of metabolism for MAIT cell functional responses 9 . Our group and others have demonstrated that MAIT cells are reliant on glycolysis to support their production of IFNg and Granzyme B 10,11,12 , whereas IL-17 production by MAIT cells has been linked to mitochondrial metabolism 13,14 .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, they can also be activated in a TCR-independent manner, via stimulation with cytokines such as IL-18 7,8 . Recently, several studies have highlighted the importance of metabolism for MAIT cell functional responses 9 . Our group and others have demonstrated that MAIT cells are reliant on glycolysis to support their production of IFNg and Granzyme B 10,11,12 , whereas IL-17 production by MAIT cells has been linked to mitochondrial metabolism 13,14 .…”
Section: Introductionmentioning
confidence: 99%